2008
DOI: 10.1002/pmic.200700489
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of Streptococcus thermophilus during the late stage of milk fermentation with special regard to sulfur amino‐acid metabolism

Abstract: Streptococcus thermophilus is a thermophilic lactic acid bacterium widely used as starter in the manufacture of dairy products in particular in yoghurt manufacture in combination with Lactobacillus delbrueckii ssp. bulgaricus. However, in spite of its massive use, the physiological state of S. thermophilus in milk has hardly been investigated. We established the first map of the cytosolic proteome of S. thermophilus LMG18311 grown in milk. It comprises 203 identified proteins corresponding to 32% of theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 48 publications
4
28
0
Order By: Relevance
“…A proteomic approach was used to unravel, e.g., the adap-tive behavior of S. thermophilus during milk fermentation. That study revealed a strong regulation of sugar metabolism pathways and induction of the transport and biosynthetic pathways for sulfur-containing amino acids (610). Despite the insight generated, the study did not reflect the most predominant industrial application of S. thermophilus, namely, coculture with Lb.…”
Section: Applications Of Functional Genomic Technologies In Situmentioning
confidence: 95%
“…A proteomic approach was used to unravel, e.g., the adap-tive behavior of S. thermophilus during milk fermentation. That study revealed a strong regulation of sugar metabolism pathways and induction of the transport and biosynthetic pathways for sulfur-containing amino acids (610). Despite the insight generated, the study did not reflect the most predominant industrial application of S. thermophilus, namely, coculture with Lb.…”
Section: Applications Of Functional Genomic Technologies In Situmentioning
confidence: 95%
“…Stock cultures of S. thermophilus LMD-9, S. thermophilus LMG18311, and L. bulgaricus ATCC11842 were prepared in reconstituted 10% (w/v) Nilac skim milk (NIZO, Ede, The Netherlands) as described previously (19). S. thermophilus monocultures and S. thermophilus/L.…”
Section: Methodsmentioning
confidence: 99%
“…For many LAB including S. thermophilus, the hydrolysis of milk caseins (i.e. the AA supply) mostly depends on the activity of a cell-wall-anchored proteinase [7]. S. thermophilus and L. bulgaricus, lead to positive effects on the yogurt taste and aroma by symbiotic coexistence, described by the ecological term protocooperation (where two species interact with each other beneficially).…”
Section: Introductionmentioning
confidence: 99%